Media Interaktif Bahasa Jawa untuk Meningkatkan Literasi Bahasa Daerah Anak Usia Dini - Nurul Fauziah; Erni Munastiwi (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2025)
The decline in the use of Javanese in the environment has made educators aware of the importance of media innovation to improve regional language literacy. This is a form of institutional support to preserve regional languages, because regional languages ​​need to be introduced to the next generation from an early age. The purpose of this study is to develop a Javanese language media to facilitate educators in introducing regional literacy to children. The research subjects were 15 children and was conducted at Masyithoh II Sanansari Kindergarten. This study used a development model or Research and Development (R&D) in the form of ADDIE which went through five stages: 1) Analysis; 2) Design; 3) Development; 4) Implementation; 5) Evaluation. The results of the study were in the form of the development of Javanese language media called "SiBaJa (Sinau Basa Jawa)". The development of this media showed that there was a feasibility score of 84% from material experts and 96.25% from media experts. The results of the effectiveness test showed a significant increase in Javanese language literacy skills with an average pretest score of 52.6% to a posttest score of 88.1%. Therefore, it can be concluded that this research can be used as a means of supporting cultural and regional language literacy. The implications for early childhood education (PAUD) teachers include the importance of innovation in the use of learning media using simple technologies such as PowerPoint to instill cultural and regional language values ​​from an early age.